Dealing with Covid-19: Between Risk and Anxiety in Students - Rachmat Chusnul Choeron; Arie Jefry Ka'arayeno (STIKes Patria Husada Blitar, 2022)
The COVID-19 pandemic has had a serious psychological impact on people around the world, especially those at high risk of contracting COVID-19. The purpose of this research was to determine the correlation between risk and student anxiety in dealing with the Covid-19 outbreak. The research design used a cross sectional study with a student population of the Faculty of Health, Tribhuwana Tunggadewi University, Malang. The sample size of 93 respondents was taken by simple random sampling. The data were collected using a questionnaire and the HARS scale. The data were analyzed by Spearman's test with =0.05. The results showed that students of the Faculty of Health Sciences, Tribhuwana Tunggadewi University had a risk of contracting Covid-19 at a median of 3.0 (minimum-maximum = 1-6) and had anxiety at a median of 7.0 (minimum-maximum = 0-27). The results of the statistical test showed that there was a significant correlation between the risk of contracting Covid-19 and anxiety in the students of the Faculty of Health Sciences, Tribhuwana Tunggadewi University, Malang (p = 0.000; r = 0.360). Correct education about Covid-19 is very important to be given to the public so that there is no misunderstanding so that it can provide peace.